2015
DOI: 10.17245/jdapm.2015.15.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI deficiency and orthognathic surgery: a case report on anesthesia management

Abstract: Factor XI deficiency (Hemophilia C) is a very rare autosomal recessive bleeding disorder. Patients with factor XI deficiency do not typically show any spontaneous bleeding or specific symptoms. Sometimes those who have this disorder are identified during special situations such as trauma or surgery. Orthognathic surgery is particularly associated with a high bleeding risk. Therefore, great care must be taken when treating patients with bleeding disorders such as factor XI deficiency. There are a few reports th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…In patients with FXI deficiency, spontaneous bleeding is rare and bleeding risk is poorly correlated with plasma levels of FXI 10 . In most cases, patients with FXI deficiency do not exhibit symptoms or require treatment, and the only clinical manifestation is an increased tendency for mild bleeding after serious injury or surgery 11–13 . Importantly, clinical, preclinical, and epidemiologic studies have shown that FXI deficiency is associated with reduced risk of adverse cardiovascular events and venous thromboembolism 14–18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with FXI deficiency, spontaneous bleeding is rare and bleeding risk is poorly correlated with plasma levels of FXI 10 . In most cases, patients with FXI deficiency do not exhibit symptoms or require treatment, and the only clinical manifestation is an increased tendency for mild bleeding after serious injury or surgery 11–13 . Importantly, clinical, preclinical, and epidemiologic studies have shown that FXI deficiency is associated with reduced risk of adverse cardiovascular events and venous thromboembolism 14–18 .…”
Section: Introductionmentioning
confidence: 99%
“… 10 In most cases, patients with FXI deficiency do not exhibit symptoms or require treatment, and the only clinical manifestation is an increased tendency for mild bleeding after serious injury or surgery. 11 , 12 , 13 Importantly, clinical, preclinical, and epidemiologic studies have shown that FXI deficiency is associated with reduced risk of adverse cardiovascular events and venous thromboembolism. 14 , 15 , 16 , 17 , 18 In contrast, a large, population‐based, case‐control study (the Leiden Thrombophilia Study) found that patients who had suffered a deep vein thrombosis had significantly higher FXI levels compared with healthy controls, with the risk of thromboembolism doubled for individuals with FXI levels above the 90th population percentile compared with those who had lower values.…”
Section: Introductionmentioning
confidence: 99%
“…Participants remained at the clinical facility, and serial pharmacokinetic samples were collected for up to 72 h after study drug administration for healthy participants and for up to 96 h for participants with hepatic impairment. spontaneous bleeding events [8][9][10][11][12][13]. In contrast, individuals with elevated plasma FXI levels have been shown to be at increased risk for venous thrombosis [14].…”
Section: Methodsmentioning
confidence: 99%
“…Based on findings from clinical and preclinical models, hemostasis is not solely dependent on the FXI pathway, and FXIa inhibitors have the potential to reduce thrombus formation [ 17 20 ]. Notably, spontaneous bleeding is rare in individuals with congenital FXI deficiencies and, for these individuals, mild bleeding after a serious injury or surgery is the only clinical manifestation of FXI deficiency [ 21 23 ]. Additionally, results from in vivo and clinical studies have shown that there is a reduced risk of adverse cardiovascular events and venous thromboembolism with FXI deficiency [ 13 , 16 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%